Cadet and junior performance is associated with senior`s World Championship and Olympics achievement in judo - Junior, M. N.; Lopes-Silva, J. P.; Takito, M. Y.; Franchini, E. (Research Quarterly for Exercise and Sport, 2024)
Purpose: We determined whether cadet and junior Judo World Championship participation and medal achievement would predict senior performance at World Championship (WC) and Olympic Games (OG).